2010
DOI: 10.3390/ijms11104140
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Biocompatibility Study of Electrospun Chitosan Microfiber for Tissue Engineering

Abstract: In this work, we examined the biocompatibility of electrospun chitosan microfibers as a scaffold. The chitosan microfibers showed a three-dimensional pore structure by SEM. The chitosan microfibers supported attachment and viability of rat muscle-derived stem cells (rMDSCs). Subcutaneous implantation of the chitosan microfibers demonstrated that implantation of rMDSCs containing chitosan microfibers induced lower host tissue responses with decreased macrophage accumulation than did the chitosan microfibers alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 22 publications
0
20
1
1
Order By: Relevance
“…Other researchers, after the implantation of the material containing chitosan in its constitution, also observed the formation of blood vessels in the area of the procedure (Azab et al, 2007;Brito et al, 2009;Kang et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers, after the implantation of the material containing chitosan in its constitution, also observed the formation of blood vessels in the area of the procedure (Azab et al, 2007;Brito et al, 2009;Kang et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…However, in another study, where the chitosan membrane was associated to stem cells, there was less inflammatory response when compared to the control group. This fact may be explained by the likely immunosuppression caused by the transplanted stem cells (Kang et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Chitosan is a natural and abundant polymer that is an attractive candidate scaffolding material for tissue engineering [13,19]. Chitosan-based hydrogels have been shown to be biodegradable, non-immunogenic, and biocompatible, and therefore, they are widely used as a therapeutic scaffold for tissue engineering processes such as cell encapsulation and cell culture [27][28][29][30]. Recent studies have shown that a mixture of chitosan and glycerol phosphate disodium salt (GP) can form a hydrogel in situ at body temperature [13,31].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, the development of adjuvant tissue engineering scaffolds have considerable promise, as they potentially offer synergy between the delivery/recruitment of cells, presentation of biochemical and physio-chemical cues, 3-D morphology and mechanical and topographical stimuli to improve or replace physiological function [7]. Within the past decade, a variety of 3-D tissue engineering scaffolds have emerged; for instance, fibrous scaffolds produced from a diverse range of polymers, both natural and synthetic, have been fabricated using a variety of methods, notably electrospinning [8][9][10]. These fibrous networks, through subsequent biochemical and physiochemical modification, may present appropriate stimuli for in vivo repair [11,12].…”
Section: Self-assembling Peptides As Biomaterials For In Vivo Applicamentioning
confidence: 99%